Applying artificial neural networks (ANN) model in flash flood simulation and forcast. - Khai, Nguyen Huu; Cau, Le Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 20 No 3, 2004)
Flash floods usually happen in small basins where the measured data of flows is not enough. Determining parameters of conceptual models such as: TANK, NAM, SSARR or HEC meets a lot of difficulties. Artificial Neural Networks (ANN) model is one suitable solution to simulate and forecast flash flood.